2009
DOI: 10.1128/aem.01158-09
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactam Resistance in Salmonella Strains Isolated from Retail Meats in the United States by the National Antimicrobial Resistance Monitoring System between 2002 and 2006

Abstract: Ampicillin-resistant (Amp r ) Salmonella enterica isolates (n ‫؍‬ 344) representing 32 serotypes isolated from retail meats from 2002 to 2006 were tested for susceptibility to 21 other antimicrobial agents and screened for the presence of five beta-lactamase gene families (bla CMY , bla TEM , bla SHV , bla OXA , and bla CTX-M ) and class 1 integrons. Among the Amp r isolates, 66.9% were resistant to five or more antimicrobials and 4.9% were resistant to 10 or more antimicrobials. Coresistance to other ␤-lactam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 35 publications
(37 reference statements)
4
36
1
Order By: Relevance
“…The resistance of chicken isolates to ß-lactams AMC, FOX, AXO, and TIO was significantly greater than that of other meat isolates, whereas the turkey isolates were more resistant to KAN, AMP, FIS, CIP, and TET compared to other meat isolates (P Յ 0.05). Similar results were observed with Salmonella isolates from retail poultry meat monitoring (40). Although, in general, the pork isolates had lower resistance than the poultry isolates, their resistance to KAN, STR, AMP, FIS, and TET was significantly higher than that of the beef isolates (P Յ 0.05).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The resistance of chicken isolates to ß-lactams AMC, FOX, AXO, and TIO was significantly greater than that of other meat isolates, whereas the turkey isolates were more resistant to KAN, AMP, FIS, CIP, and TET compared to other meat isolates (P Յ 0.05). Similar results were observed with Salmonella isolates from retail poultry meat monitoring (40). Although, in general, the pork isolates had lower resistance than the poultry isolates, their resistance to KAN, STR, AMP, FIS, and TET was significantly higher than that of the beef isolates (P Յ 0.05).…”
Section: Discussionsupporting
confidence: 74%
“…In the last 10 years, this resistance phenotype has emerged in both humans and food animals in the United States (12,40,44). TIO is the only cephalosporin approved for systemic use in food animals in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to tetracycline (80.53%) and streptomycin (81.20%) tended to occur at relatively high frequencies, higher than reported by Thong and Modaressi in 2011 (73.8% and 57.9%) [11], Yildirim et al in 2011 (67.6% and 61.7%) [13], and Zhao et al in 2009, who observed resistance of S. Typhimurium to streptomycin (63%) and tetracycline (61%) [23]. A higher resistance rate to tetracycline was reported by Mahmud et al in 2011 (93%) [14].…”
Section: Discussionmentioning
confidence: 64%
“…The bla CMY-2 gene encodes a cephalomycinase that exhibits extended resistance to many ␤-lactams, including narrow-, expanded-, and broad-spectrum cephalosporins, whereas SugE has been shown to confer decreased susceptibility to quaternary ammonium compounds, including common disinfectants such as cetylpyridinium chloride (14,81). The close physical proximity of sugE to the bla CMY-2 ␤-lactamase gene is of particular public health significance, as it points to the potential coselection of linked CDS carried by extrachromosomal elements and their role in the spread of MDR phenotypes among veterinary and human pathogens.…”
Section: ) (33)mentioning
confidence: 99%